The paediatric version of Wisconsin Gait Scale, adaptation for children with hemiplegic cerebral palsy: a prospective observational study - Guzik, Agnieszka; Drużbicki, Mariusz; Kwolek, Andrzej; Przysada, Grzegorz; Bazarnik-Mucha, Katarzyna; Szczepanik, Magdalena; Wolan-Nieroda, Andżelina; Sobolewski, Marek (My University, 2017)
In clinical practice there is a need for a specific scale enabling detailed and multifactorial assessment of gait in children with spastic hemiplegic cerebral palsy. The objective of the study is to assess the Wisconsin Gait Scale (WGS) in terms of its inter- and intra-observer reliability in observational gait analysis of children with hemiplegic cerebral palsy. The study was conducted in a group of 34 patients with hemiplegic cerebral palsy. At the first stage the original version of WGS was used to assess gait. At the second stage a modified WGS was introduced and the same video recordings were rescored using the new, paediatric version of WGS. Three independent examiners performed the assessment twice (two weeks apart). Inter and intra-observer reliability of the modified WGS were determined. The findings show very high inter- and intra-observer reliability of the modified WGS. This was reflected by a lack of systematically oriented differences between the repeated measurements, very high value of Spearman's rank correlation coefficient 0.9  |R| < 1, very high value of ICC > 0.9, and low value of CV< 2.5% for the specific physical therapists. The new, paediatric version of WGS is a promising tool to be used in qualitative observational gait assessment of children with spastic hemiplegic cerebral palsy. The findings of the study have practical value as they show feasibility of the new, affordable, easy-to-use tool for gait assessment to be used in clinical practice specifically for children with spastic hemiplegic cerebral palsy.
Keywords: hemiplegic gait; cerebral palsy; Wisconsin Gait Scale; intra-observer reliability; inter-observer reliability; scale adaptation